GRAPHIC DESIGN INNOVATION AS A CREATIVE STRATEGY IN TAX EDUCATION AT UMKM IN SARIJADI VILLAGE, BANDUNG CITY - Roni Surahman; Dini Paryanti (INFOKOM (Informatika & Komputer), 2025)
This study aims to explore graphic design innovation as a creative strategy in tax education for UMKM in Sarijadi Village, Bandung City. The research uses a qualitative approach with a case study method, where data is collected through interviews with UMKM actors and observations of tax education materials based on graphic design that have been implemented. The discussion covers the role of graphic design in enhancing tax understanding among UMKM actors and how visually appealing and easy-to-understand designs can effectively convey tax information. The research findings indicate that graphic design innovation plays a significant role in increasing UMKM actors' interest in complying with tax obligations, as the presented material is more accessible and engaging. The conclusion of this study is that creative graphic design can serve as an effective educational tool to improve tax compliance among UMKM, particularly at the village level, by offering a more engaging and informative approach. Therefore, the application of graphic design in tax education is highly recommended for broader implementation in UMKM across other regions.